The Prophetic’s Humanization Values in Indonesian Junior High School Textbook - Ubaidullah Ubaidullah; Darmanto Darmanto (Indonesian Publication Center, 2020)
The prophetic's humanization values refer to the values that human have to be moral, wise, honest, fair, intelligent, independent, and contributive. This study aims at describing the forms of prophetic humanization values in the Indonesian Junior High School textbook written by Kosasih dan Restuti. This study applied a descriptive qualitative method. Furthermore, this study is library research. The data collection techniques were reading techniques, tapping techniques, and note-taking techniques. Those three techniques carried out to elaborate on collecting data to obtain data validity. The results of the current study indicate that the finding of the prophetic's humanization values in the Indonesian Junior High School textbook written by Kosasih dan Restuti. The prophetic's humanization values are the cooperation value, the friendship value, the honesty value, the tolerance value of, and the politeness value.